Rehabilitation of severe hereditary gingival hyperplasia with virtual surgical planning and computer-assisted surgery - N. Lynch; I. Liau; A. Cheng; P. Duke (Elsevier, 2021)
Virtual surgical planning and computer-assisted surgery have various applications and demonstrable benefits in craniomaxillofacial surgery. We report the complex rehabilitation of a severe case of hereditary gingival hyperplasia utilizing virtual surgical planning and computer-aided design and manufacturing (CAD/CAM) for the ablative, reconstructive and prosthetic components of the case.